FINANCIAL PERFORMANCE ANALYSIS AT PT. BANK MEGA TBK IN THE FINANCIAL INDUSTRY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2021 - Fachrunnisa Ernanda Manurung; Adha Aulia; Cut Millisa; Putri Pratiwi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Study This aim For know Performance Finance reviewed from ratio Liquidity, solvency, and Profitability of PT. Bank Mega Tbk registered on the Stock Exchange Indonesia in 2019 – 2021. To find out the development of the Financial Performance of PT. Bank Mega Tbk in Look from ratio Liquidity, Solvability And Profitability year 2019-2021. How performance financial seen from ratio Liquidity, Solvability And Profitability year 2019–2021 on PT. Bank Mega Tbk compared to standard ratio finance. Study This using quantitative data analysis in order to solve the problems raised in this research, specifically the ratio of liquidity, solvency and profitability. Research results : In general financial performance of PT. Bank Mega, Tbk based on the results of the quick ratio liquidity ratio, banking ratio And loans to deposits ratio can said Good Because capable fulfil obligation period in short although experience decline And fluctuation every the year.The solvency ratio is also quite good because it is able to meet short-term obligations as well as in the long term, even though the primary ratio and capital deficiency ratio are experiencing enhancement And change as well as exists fluctuation. For results ratio profitability can also said to be good because it is able to generate profits where the net profit margin and return on equity capital has increased and there have been fluctuations in return on assets and net interest margin. 2) The development of the ratio of liquidity and profitability of PT. Bank Mega, Tbk Not yet so efficient matter This because development in every ratio liquidity, solvency And profitability is not so stable, the result is that some have decreased and some have has increased every year. 3) Comparison of the standard ratio of the ratio results liquidity, solvency And profitability PT. Bank Mega, Tbk although capable fulfil short-term and long-term obligations and can generate profits where liquidity the quick ratio, banking ratio and loans to deposit ratio did not meet the standards. For results solvency ratio on the primary ratio and capital equity ratio have met the standard. For profitability on the net profit margin, return on equity capital and return on assets is sufficient standard ratio whereas For net interest margins not up to standard ratio.